High-salt organic wastewater degradation composite catalyst

A composite catalyst with alumina-based metal ions enhances high-salt organic wastewater treatment by increasing degradation rates and reducing by-products and energy use, addressing treatment challenges.

CN119186653APending Publication Date: 2024-12-27WUXI YUZHIYUAN ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411449388.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

High-salt organic wastewater is difficult to treat due to its inhibitory effect on microorganisms and membrane pollution, leading to reduced treatment efficiency and environmental pollution.

Method used

A composite catalyst is developed using alumina as a carrier with high specific surface area and strong chemical stability, where metal ions are fixed and characterized to enhance catalytic performance, characterized through physicochemical analysis, and evaluated for effective degradation of organic pollutants.

Benefits of technology

The catalyst significantly increases the degradation rate of organic pollutants, reduces by-products, and decreases energy consumption and chemical use, improving treatment efficiency and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186653A_ABST
    Figure CN119186653A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field, in particular to a high-salt organic wastewater degradation composite catalyst. According to the technical scheme, the method comprises the steps of carrier selection, catalyst preparation and catalyst characterization and performance evaluation, the carrier selection comprises the steps of selecting a carrier aluminum oxide with high specific surface area, good pore structure and high chemical stability according to the characteristics of the high-salinity organic wastewater, and fixing metal ions on the carrier through catalyst preparation, and carrying out physicochemical property characterization on the prepared composite catalyst in a catalyst characterization mode, analyzing the chemical state of active components of the catalyst, and evaluating the catalyst through the performance evaluation. Through research and development of the high-salt organic wastewater degradation composite catalyst, the wastewater treatment efficiency can be improved, the cost can be reduced, resource recovery can be promoted, and the environment can be protected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field, and in particular to a composite catalyst for degrading high-salt organic wastewater. Background Art

[0002] High-salt organic wastewater mainly comes from the chemical, pharmaceutical, printing and dyeing and other industries. This type of wastewater contains high concentrations of salt, organic matter, heavy metal ions and other pollutants. If it is discharged directly without treatment, it will cause serious pollution to the environment. High-salt organic wastewater refers to wastewater containing higher concentrations of salt and organic matter. This type of wastewater has a wide range of sources, is difficult to treat, and poses serious harm to the environment. Through infiltration, harmful substances in the wastewater will pollute the soil, affect soil structure and fertility, and even cause soil salinization.

[0003] High-salt environments have an inhibitory effect on the activity of microorganisms, resulting in reduced efficiency of traditional biochemical treatment methods and difficulty in effectively degrading organic matter in wastewater. In membrane separation technology, salt and organic matter can easily cause membrane pollution and blockage, reducing treatment efficiency and shortening the service life of the membrane.

[0004] To this end, we proposed a composite catalyst for the degradation of high-salt organic wastewater to solve the existing problems. Summary of the invention

[0005] The purpose of the present invention is to provide a composite catalyst for degrading high-salt organic wastewater in view of the problems existing in the background technology.

[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a composite catalyst for degrading high-salt organic wastewater, comprising carrier selection, catalyst preparation, catalyst characterization and performance evaluation, wherein the carrier selection comprises selecting a carrier alumina having a high specific surface area, a good pore structure and strong chemical stability according to the characteristics of the high-salt organic wastewater, fixing metal ions on the carrier through the catalyst preparation, characterizing the physical and chemical properties of the prepared composite catalyst through a catalyst characterization method and analyzing the chemical state of the active components of the catalyst, and evaluating the catalyst through the performance evaluation.

[0007] Preferably, the catalyst preparation steps include active component solution preparation, impregnation process, filtration and washing, drying, roasting, cooling and screening. Through the above steps, a catalyst with specific catalytic performance can be prepared.

[0008] Preferably, the preparation of the active component solution includes selecting a metal nitrate according to the active component of the desired catalyst, and dissolving 8.48g of the metal salt in 0.848ml of an alcohol solvent to complete the solution preparation operation, adding 100g of the pretreated carrier to the active component solution, and keeping it immersed at room temperature for 24 hours to allow the active component to be fully adsorbed to the surface of the carrier, then filtering the impregnated carrier to separate the solution, washing the carrier with deionized water to remove the unabsorbed active component and impurities, drying the washed carrier at 50°C to remove moisture, placing the dried carrier in a calcining furnace, and calcining it at 500°C. During the calcining process, the active component reacts chemically with the carrier to form a substance with catalytic activity. After the calcination is completed, the catalyst is allowed to cool naturally to room temperature, and finally the catalyst is sieved to remove powder and fine particles to ensure that the catalyst has a certain particle size range.

[0009] Preferably, the chemical reaction between the active component and the carrier can be divided into dehydration and degassing, redox reaction, phase transition, solid phase reaction, sintering and agglomeration. These reactions form catalytically active substances with specific chemical composition, structure and morphology. These substances can provide suitable surface properties and active sites to promote the target chemical reaction.

[0010] Preferably, the catalyst characterization includes characterization of physicochemical properties and chemical states of catalyst active components. The physicochemical property characterization includes specific surface area, pore structure analysis and dispersibility of active components. These characterization techniques can provide detailed information of the composite catalyst, help researchers optimize the design and preparation process of the catalyst, and thus improve its catalytic performance.

[0011] Preferably, the chemical state of the active components of the catalyst is usually analyzed using the characterization technique of X-ray diffraction, which can deeply explore the active sites and catalytic mechanism of the catalyst, thereby guiding the design and optimization of the catalyst.

[0012] Preferably, the performance evaluation includes setting experimental conditions, comparative experiments, and analyzing results, wherein a high-salt organic wastewater sample is obtained, the pH value of the wastewater is adjusted to the optimal action range of the catalyst, a certain amount of catalyst is weighed and prepared to be added to the reactor, the prepared wastewater is poured into the reactor, the stirring device is turned on, the catalyst is added, the timing is started, the set temperature and pH value are maintained, the reaction conditions are ensured to be stable, sampling is performed at predetermined time points, and analysis is performed immediately, the organic concentration in the wastewater is analyzed using an HPLC instrument, the change in organic concentration at each time point is recorded, and parameters such as degradation rate and reaction rate are calculated. To ensure the reliability of the experimental results, repeated experiments should be performed and the average value calculated. Under the same conditions, the experiment is performed without adding a catalyst to exclude the influence of other factors on the degradation of wastewater.

[0013] Preferably, the analysis results include setting a series of time points, such as 0 minutes, 30 minutes, 60 minutes, 120 minutes, etc., to evaluate the degradation effect at different time points. At the preset time points, wastewater samples are collected from the experimental group and the control group, and the organic matter concentration in the wastewater is analyzed using high performance liquid chromatography, and the degradation rates of the experimental group and the control group at different time points are compared.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] The high-salt organic wastewater degradation composite catalyst of the present invention accelerates the reaction rate during use: the composite catalyst can significantly increase the degradation rate of organic pollutants in high-salt organic wastewater, shorten the treatment time, and improve the treatment efficiency;

[0016] Improve the degree of degradation: The composite catalyst helps to deeply degrade organic matter and can convert difficult-to-degrade organic matter into harmless or easily biodegradable small molecules;

[0017] Reduce by-products: Catalysts can selectively promote specific reaction pathways, reduce the generation of by-products, and reduce the risk of secondary pollution;

[0018] Reduced use of chemicals: The use of catalysts can reduce the amount of chemicals required in traditional treatment processes and reduce potential impact on the environment;

[0019] Reduce carbon emissions: By improving energy efficiency and reducing energy consumption, composite catalysts help reduce greenhouse gas emissions during the treatment process. In summary, the study of composite catalysts for the degradation of high-salt organic wastewater is of great significance for improving wastewater treatment efficiency, reducing costs, promoting resource recovery, protecting the environment, and promoting the development of related technologies and industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the process structure of the present invention; DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Embodiment 1

[0023] like Figure 1As shown, a high-salt organic wastewater degradation composite catalyst proposed in the present invention includes carrier selection, catalyst preparation, catalyst characterization and performance evaluation. The carrier selection includes selecting a carrier alumina with high specific surface area, good pore structure and strong chemical stability according to the characteristics of the high-salt organic wastewater, fixing metal ions on the carrier through catalyst preparation, characterizing the physical and chemical properties of the prepared composite catalyst through catalyst characterization and analyzing the chemical state of the catalyst active components, and evaluating the catalyst through performance evaluation.

[0024] Embodiment 2

[0025] like Figure 1 As shown, a high-salt organic wastewater degradation composite catalyst proposed by the present invention, compared with Example 1, this embodiment also includes: the catalyst preparation steps include active component solution preparation, impregnation process, filtration and washing, drying, roasting and cooling and screening. Through the above steps, a catalyst with specific catalytic performance can be prepared.

[0026] First, it is necessary to determine the theoretical loading amount of the active component in the catalyst, which is usually expressed as the mass of the active component per unit carrier (such as g metal / 100g carrier). According to the loading amount of the active component and the purity of the metal salt, the mass of the required metal salt is calculated. This usually involves the following calculations: determine the molar mass of the metal salt, calculate the number of moles of the required metal salt according to the required loading amount of the active component, multiply it by the molar mass of the metal salt, and obtain the mass of the required metal salt. According to the solubility of the metal salt and the requirements of subsequent treatment, select a suitable solvent and determine the concentration of the solution. According to the calculated amount of metal salt and the selected solvent concentration, prepare the active component solution. In summary, it is expressed as follows:

[0027] The preparation of the active component solution includes selecting a metal nitrate according to the active component of the desired catalyst, and dissolving 8.48g of the metal salt in 0.848ml of an alcohol solvent to complete the solution preparation operation, adding 100g of the pretreated carrier to the active component solution, and keeping it immersed at room temperature for 24 hours to allow the active component to be fully adsorbed to the surface of the carrier, and then filtering the impregnated carrier to separate the solution, washing the carrier with deionized water to remove the unabsorbed active component and impurities, drying the washed carrier at 50°C to remove moisture, placing the dried carrier in a calcining furnace, and calcining it at 500°C. During the calcining process, the active component reacts chemically with the carrier to form a substance with catalytic activity. After the calcination is completed, the catalyst is allowed to cool naturally to room temperature, and finally the catalyst is sieved to remove powder and fine particles to ensure that the catalyst has a certain particle size range.

[0028] The chemical reaction between the active component and the carrier can be divided into dehydration and degassing. During the heating process, the physically adsorbed water in the carrier and the crystal water in the active component are first removed. If there are organic substances in the active component or the carrier, such as surfactants, stabilizers, etc., these substances will decompose and volatilize during the roasting process. The carbonates in the carrier or active component will decompose at high temperature and release gases such as carbon dioxide.

[0029] Redox reaction: When calcined in air, metal precursors may be oxidized to form metal oxides. In an oxygen-deficient or reducing atmosphere, some oxides may be reduced to metallic states or low-valent oxides.

[0030] Crystal phase transition: During the calcination process, the active components may transform from an amorphous state to a form with a more perfect crystal structure. At high temperatures, lattice defects are reduced, lattice parameters are adjusted, grains grow, and a more stable crystal structure is formed;

[0031] Solid phase reaction: The active components may react with oxygen or hydroxyl groups on the surface of the carrier to form new chemical bonds. The active components may enter the crystal lattice of the carrier to form a solid solution, which can enhance the dispersion and stability of the active components on the carrier.

[0032] Sintering and agglomeration: At high temperatures, active component particles may sinter, resulting in particle agglomeration or the formation of larger particles. During the calcination process, the particles may rearrange, affecting the pore structure and specific surface area of ​​the catalyst. These reactions form catalytically active substances with specific chemical composition, structure and morphology. These substances can provide suitable surface properties and active sites to promote the target chemical reaction.

[0033] Embodiment 3

[0034] like Figure 1 As shown, the composite catalyst for degradation of high-salt organic wastewater proposed by the present invention, compared with the first embodiment, this embodiment also includes:

[0035] Catalyst characterization includes characterization of physicochemical properties and the chemical state of the active components of the catalyst. The physicochemical properties characterization includes specific surface area, pore structure analysis and dispersion of active components. These characterization techniques can provide detailed information on composite catalysts and help researchers optimize the design and preparation process of catalysts, thereby improving their catalytic performance. The specific steps for specific surface area are as follows:

[0036] The pretreated sample is cooled to liquid nitrogen temperature (about -196°C). At this low temperature, nitrogen is passed through the sample, and the adsorption amount of nitrogen under different pressures is recorded. By changing the pressure of the system, a series of adsorption data points can be obtained, which constitute the adsorption isotherm.

[0037] The BET equation is used to analyze the adsorption isotherm. The BET equation is a linear equation about relative pressure (P / P0) and is in the following form:

[0038]

[0039] Where P is the gas pressure, P0 is the gas saturated vapor pressure, V is the adsorption capacity, Vm is the maximum volume of monolayer adsorption, and C is the BET constant.

[0040] by is the vertical axis, Plot the horizontal axis and perform linear regression analysis. Vm and C can be calculated from the intercept and slope of the linear regression line. Once Vm is obtained, the molecular area of ​​monolayer adsorption can be calculated (by knowing the molecular size).

[0041] Specific surface area (m 2 / g) can be calculated by the following formula:

[0042]

[0043] Among them, N A is Avogadro's constant and S is the molecular area of ​​monolayer adsorption.

[0044] Specific steps for pore structure analysis:

[0045] After sample preparation, place the sample in a dedicated sample tube or container. Before testing, the sample may need to be pretreated at a certain temperature to remove impurities and moisture adsorbed on the surface. Use a calibration sample with a known pore structure to calibrate the mercury intrusion meter. Place the sample in the sample chamber of the mercury intrusion meter and gradually increase the pressure to allow mercury to enter the pores of the sample. Record the intrusion volume of mercury under different pressures. The pore size distribution can be obtained through the relationship between pressure and intrusion volume.

[0046] Specific steps for analyzing the dispersed pore structure of active components:

[0047] The catalyst sample is ground into powder, the powder sample is dispersed in ethanol or other appropriate solvents, the dispersion is dropped onto the microgrid, and the test is performed after the solvent evaporates. The microgrid is placed on the sample rod of the transmission electron microscope, and the parameters of the microscope, including magnification, focal length and electron beam intensity, are adjusted to obtain high-resolution TEM images, and the particle size and distribution of the active components are observed. The particle size analysis of the active component particles is performed using image analysis software, and the average size, size distribution and dispersion of the particles are calculated.

[0048] The chemical state of the active components of a catalyst is usually analyzed using X-ray diffraction characterization technology, which can provide in-depth insights into the active sites and catalytic mechanisms of the catalyst, thereby guiding the design and optimization of the catalyst.

[0049] Embodiment 4

[0050] like Figure 1 As shown, the composite catalyst for degradation of high-salt organic wastewater proposed by the present invention, compared with the first embodiment, this embodiment also includes:

[0051] The performance evaluation includes setting experimental conditions, comparative experiments, and analysis results. A high-salt organic wastewater sample is obtained, the pH value of the wastewater is adjusted to the optimal range of the catalyst, a certain amount of catalyst is weighed, and it is prepared to be added to the reactor. The prepared wastewater is poured into the reactor, the stirring device is turned on, the catalyst is added, the timing is started, the set temperature and pH value are maintained, and the reaction conditions are ensured to be stable. Samples are taken at predetermined time points and analyzed immediately. The concentration of organic matter in the wastewater is analyzed using an HPLC instrument, and the changes in the concentration of organic matter at each time point are recorded. Parameters such as the degradation rate and the reaction rate are calculated. To ensure the reliability of the experimental results, repeated experiments should be carried out and the average value calculated. Under the same conditions, the experiment is carried out without adding a catalyst to exclude the influence of other factors on the degradation of wastewater. The analysis results include setting a series of time points, such as 0 minutes, 30 minutes, 60 minutes, 120 minutes, etc., to evaluate the degradation effect at different time points. At the preset time points, wastewater samples are collected from the experimental group and the control group, and the organic matter concentration in the wastewater is analyzed using high-performance liquid chromatography. The degradation rates of the experimental group and the control group at different time points are compared. The calculation formula is as follows:

[0052]

[0053] The above-mentioned specific embodiments are only several preferred embodiments of the present invention. Based on the technical solutions of the present invention and the relevant inspirations of the above-mentioned embodiments, those skilled in the art can make various alternative improvements and combinations to the above-mentioned specific embodiments.

[0054] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A composite catalyst for degradation of high-salt organic wastewater, including carrier selection, catalyst preparation, catalyst characterization and performance evaluation, characterized in that: The carrier selection includes selecting a carrier alumina with high specific surface area, good pore structure and strong chemical stability according to the characteristics of high-salt organic wastewater, fixing metal ions on the carrier through the catalyst preparation, characterizing the physical and chemical properties of the prepared composite catalyst and analyzing the chemical state of the active components of the catalyst through a catalyst characterization method, and evaluating the catalyst through the performance evaluation.

2. The high-salt organic wastewater degradation composite catalyst according to claim 1, characterized in that: The catalyst preparation steps include active component solution preparation, impregnation process, filtration and washing, drying, roasting, cooling and screening. Through the above steps, a catalyst with specific catalytic performance can be prepared.

3. A high-salt organic wastewater degradation composite catalyst according to claim 2, characterized in that: The preparation of the active component solution includes selecting a metal nitrate according to the active component of the desired catalyst, and dissolving 8.48g of the metal salt in 0.848ml of an alcohol solvent to complete the solution preparation operation, adding 100g of a pretreated carrier to the active component solution, and keeping it immersed at room temperature for 24 hours to allow the active component to be fully adsorbed to the surface of the carrier, then filtering the impregnated carrier to separate the solution, washing the carrier with deionized water to remove the unabsorbed active component and impurities, drying the washed carrier at 50°C to remove moisture, placing the dried carrier in a calcining furnace, and calcining it at 500°C. During the calcining process, the active component reacts chemically with the carrier to form a substance with catalytic activity. After the calcination is completed, the catalyst is allowed to cool naturally to room temperature, and finally the catalyst is sieved to remove powder and fine particles to ensure that the catalyst has a certain particle size range.

4. A high-salt organic wastewater degradation composite catalyst according to claim 2, characterized in that: The chemical reactions between the active components and the carrier can be divided into dehydration and degassing, redox reaction, phase transition, solid phase reaction, sintering and agglomeration. These reactions form catalytically active substances with specific chemical composition, structure and morphology. These substances can provide suitable surface properties and active sites to promote the target chemical reaction.

5. The high-salt organic wastewater degradation composite catalyst according to claim 1, characterized in that: The catalyst characterization includes the characterization of physicochemical properties and the chemical state of the catalyst active components. The physicochemical property characterization includes specific surface area, pore structure analysis and active component dispersion. These characterization techniques can provide detailed information of the composite catalyst, help researchers optimize the design and preparation process of the catalyst, and thus improve its catalytic performance.

6. A composite catalyst for degradation of high-salt organic wastewater according to claim 5, characterized in that: The chemical state of the active components of the catalyst is usually analyzed using the characterization technique of X-ray diffraction, which can deeply explore the active sites and catalytic mechanism of the catalyst, thereby guiding the design and optimization of the catalyst.

7. The high-salt organic wastewater degradation composite catalyst according to claim 1, characterized in that: The performance evaluation includes setting experimental conditions, comparative experiments, and analyzing results, wherein a high-salt organic wastewater sample is obtained, the pH value of the wastewater is adjusted to the optimal action range of the catalyst, a certain amount of catalyst is weighed and prepared to be added to the reactor, the prepared wastewater is poured into the reactor, the stirring device is turned on, the catalyst is added, the timing is started, the set temperature and pH value are maintained, the reaction conditions are ensured to be stable, sampling is performed at predetermined time points, and analysis is performed immediately, the organic matter concentration in the wastewater is analyzed using an HPLC instrument, the change in the organic matter concentration at each time point is recorded, and parameters such as the degradation rate and the reaction rate are calculated. To ensure the reliability of the experimental results, repeated experiments should be performed and the average value calculated. Under the same conditions, the experiment is performed without adding a catalyst to exclude the influence of other factors on the degradation of the wastewater.

8. The high-salt organic wastewater degradation composite catalyst according to claim 7, characterized in that: The analysis results include setting a series of time points, such as 0 minutes, 30 minutes, 60 minutes, 120 minutes, etc., to evaluate the degradation effect at different time points. At the preset time points, wastewater samples are collected from the experimental group and the control group, and the organic matter concentration in the wastewater is analyzed using high performance liquid chromatography, and the degradation rates of the experimental group and the control group at different time points are compared.